Modeling of dual-band bandpass filter with triangular shaped DGS / Nur Wahida Miskon - Miskon, Nur Wahida
This paper proposed a dual-band bandpass filter with triangular shaped defective ground structure (DGS). The filter topology made up of a coupled-line connected directly to line impedance with a same structure connected in parallel which produce a dual-path filter design. Triangular shaped DGS is added to the design in order to observe the changes in frequency response. It is found that the implementation of triangular shaped DGS improves the first passband with centre frequency of 1.086 GHz when compared with non DGS filter. The optimised size of the DGS is ISO mm2 located at the centre and at the quarter wavelength lines of the filter.